2005
DOI: 10.1213/01.ane.0000149901.42804.92
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Interscalene Analgesia After Shoulder Surgery: Catheter Insertion by the Posterior Approach

Abstract: Insertion and maintenance of an interscalene catheter is technically challenging using lateral or anterior approaches. We report a technique to provide continuous brachial plexus blockade through a 48-h infusion of ropivacaine 0.1% (5 mL/h with a 5 mL bolus dose, 20-min lockout interval) using a catheter inserted with cannula-over-needle technique on the posterior side of the neck in 120 patients undergoing shoulder surgery. All catheters were successfully placed. There were no technical complications (impossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…16% (4/25) and 12% (2/17) reported by Ilfeld et al18) and Delaunay et al,19) respectively. However, these incidences were higher than those reported by Sandefo et al20) via the posterior approach, only 0.8% (1/122). Generally, mobilization exercises of the shoulder begin from one day after surgery for rotator cuff repair.…”
Section: Discussioncontrasting
confidence: 63%
“…16% (4/25) and 12% (2/17) reported by Ilfeld et al18) and Delaunay et al,19) respectively. However, these incidences were higher than those reported by Sandefo et al20) via the posterior approach, only 0.8% (1/122). Generally, mobilization exercises of the shoulder begin from one day after surgery for rotator cuff repair.…”
Section: Discussioncontrasting
confidence: 63%
“…Some might question using a Tuohy needle given this problem and might advocate a long bevel needle to facilitate muscle penetration. 24 However, Boezaart and Franco 25 and Boezaart 26 highlighted the fact that sharp needles be avoided around the neuraxis because dural cuffs can extend along the nerve roots at this level: Tuohy needles providing some protection from penetrating these cuffs with consequent subarachnoid block, or worse, intracordal injection.…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of the local anesthetic concentration/volume versus dose has significant clinical consequences given the wide range of local anesthetic concentrations used for perineural infusion [5,14,15]. Le et al [16] reported that for CISB, a lower concentration of local anesthetic at a higher basal rate provided superior analgesia.…”
Section: Discussionmentioning
confidence: 99%